Experimental investigation of the output power of PV panels combined with circular configuration TEG modules using LED bulb loads - Mustofa, Mustofa; Iskandar, Iskandar; Rahman, Yuli Asmi; Muchsin, Muchsin; Medi, Gery; Rusdi, M.; Diana, Diana (Program Studi Teknik Elektro Universitas Khairun, 2025)
The purpose of this study is to optimize the potential of solar energy that releases light and thermal energy simultaneously by using a combination of PV and TEG technology. PV only absorbs photon light, where solar thermal is transmitted to the TEG module under the panel surface which is useful for maintaining temperature and increasing PV output power. The TEG module configuration was chosen to be circular with the diameter of the circle adjusting to the area of the solar PV panel. There are two PV panels used during the test, one panel is left without TEG and the other panel is installed with 12 TEG modules and on the cold side of the module is added a heat sink and circulating water fluid cooling to maintain the temperature of the cold side of the module. The test results show that the integration of PV-TEG increases the system output power by about 45% compared to PV alone. The PV surface temperature is more stable and tends to be even with the attachment of TEG and cooling with water, while without the hybrid, the PV temperature appears to be sinusoidal with a peak temperature of about 70°C compared to the hybrid only around 40 and 50°C. PV temperatures below 60°C are important to maintain PV performance for a long period